Perception of spirituality, religiosity, and euphemia in the light of hospitalized patients - Camillo, Nadia Raquel Suzini (2021)
Objective: to apprehend patients’ perception of spirituality, religiosity, and the practice of euphemia throughout hospitalization. Methods: qualitative research, conducted with 12 hospitalized patients. Data collection took place through individual interviews. The speeches were transcribed in full, submitted to thematic content analysis, and the discussion was based on the Transpersonal Care theory. Results: from the speeches, three categories emerged: Spirituality and religiosity: meaning and balm to human life; Benefits of the practice of euphemia in the hospital environment; Spirituality, religiosity, and euphemia in the art of nursing care: biopsychosocial triad in the patient’s perception. Conclusion: spirituality, religiosity, and euphemia were configured as a biopsychosocial triad capable of attributing meaning, foundation, and balm to human life. Also, it may encourage patients and nursing professionals to face the adversities of the hospital environment.